Analysis of urban land utilize by using optimization algorithm based on biogeography Case study: Semnan County - mehrnaz rezvani; yosefali ziari; naser eghbali; hosein mojtabazade khanghahi (تحقیقات کاربردی علوم جغرافیایی)
Urban land utilize planning, for optimal use of existing facilities and urban spaces is one of the main cores of urban planning, which is usually defined as a multi-objective issue. In line with the absence of specific categorization, system for land use in Iran the use of metaheuristic algorithm and artificial intelligence is required. One of the algorithms that introduced and used in recent years are the optimization algorithm (BBO) based on biogeography. Current research is from practical research group and type of descriptive-analytic research, the data analysis method would be write and execute in MATLAB software by using biogeography algorithm. The purpose, after identifying most effective variable, will be to improve the present status of the system's distribution use indicators and their adjacency in the county surface. For comparing the results of current research, in terms of desired area needed uses with development plan of Semnan County, each dimension of (GIS) layer should be provide.overlapping of the layers would be compare with development design.